Anatomical Considerations in Multiligament Knee Injury and Surgery - Dwyer, Tim; Whelan, Danny (The Journal of Knee Surgery, 2012)
The management of multiligament knee injury mandates a comprehensive understanding of the anatomy on all sides of the joint. Imperative to repair or reconstructive procedures is an intimate knowledge of the structure of the cruciate and collateral ligaments, as well as the complex confluence of structures that comprise the posteromedial and posterolateral corners. Beyond the ligamentous anatomy, the surgeon must also be aware of the potential for neurologic and vascular compromise—both from injury and from treatment—that can often complicate multiligament knee injuries. In this article, we outline the basic anatomy and biomechanical function of the ligamentous structures of the knee, structures at risk, and the patterns of injury seen with knee dislocations and multiple ligament knee injuries in general.
Keywords: knee; dislocation; multiligament; anatomy